Association between dietary antioxidant intake and overweight/obesity risk among children and adolescents: a cross-sectional analysis from NHANES 2011–2016 - Chen, Jinwen; Shi, Changhong (Frontiers in Nutrition, 2025)
ObjectiveOverweight and obesity among children and adolescents has emerged as a critical global public health issue. Oxidative stress, a key factor in obesity-related inflammation and metabolic dysregulation, underscore the importance of dietary antioxidants. The composite dietary antioxidant index (CDAI), which integrates vitamins A, C, E, carotenoids, selenium, and zinc, provide a comprehensive measure of overall dietary antioxidant intake. However, the relationship between CDAI and overweight/obesity in children and adolescents remains insufficient explored.MethodsThis study utilized data from the National Health and Nutrition Examination Survey (NHANES) collected between 2011 and 2016, including 17,919 participants aged 6–19 years. The CDAI were calculated based on dietary intake data from 24-hour dietary recalls. To account for total energy intake, two widely recognized adjustment methods were used: the standard regression model and the nutrient density model. In the nutrient density model, an energy-standardized CDAI (E-CDAI) was computed. Logistic regression models were conducted to examine associations between CDAI, E-CDAI, mCDAI, mE-CDAI, and overweight/obesity risk, adjusting for potential confounders such as age, gender, race, physical activity, and socioeconomic status.ResultsThe analysis showed a significant negative association between CDAI and overweight/obesity risk among adolescents aged 12–19 years. However, no significant association was observed in children aged 6–11 years. In contrast, E-CDAI showed no significant association with overweight/obesity risk in adolescents (OR = 0.87; 95% CI: 0.71–1.07). Notably, selenium exhibited a negative association with overweight/obesity in the standard regression model but a positive association in the nutrient density model. After excluding the selenium from the original 6 antioxidants included in the CDAI, the modified CDAI (mCDAI) demonstrated a significant negative association with overweight/obesity in both the standard regression model (OR = 0.74; 95% CI: 0.63–0.86) and nutrients density model (OR = 0.78; 95% CI: 0.69–0.89).ConclusionThis study developed a modified CDAI, comprising of vitamins A, C, E, carotenoids, and zinc, and identified a consistent negative association between mCDAI and overweight/obesity risk, irrespective of energy adjustment method. These findings suggest that a diet rich in antioxidants may play a protective role in preventing obesity in adolescent aged 12–19 years.